Identification and Characterization of Multiple Intermediate Alleles of the Key Genes Regulating Brassinosteroid Biosynthesis Pathways - Du, Junbo; Zhao, Baolin; Sun, Xin; Sun, Mengyuan; Zhang, Dongzhi; Zhang, Shasha; Yang, Wenyu (Frontiers in Plant Science, 2017)
Most of the early identified brassinosteroid signaling and biosynthetic mutants are null mutants, exhibiting extremely dwarfed phenotypes and male sterility. These null mutants are usually unable to be directly transformed via a routinely used Agrobacterium-mediated gene transformation system and therefore are less useful for genetic characterization of the brassinosteroid (BR)-related pathways. Identification of intermediate signaling mutants such as bri1-5 and bri1-9 has contributed drastically to the elucidation of BR signaling pathway using both genetic and biochemical approaches. However, intermediate mutants of key genes regulating BR biosynthesis have seldom been reported. Here we report our identification of several intermediate BR biosynthesis mutants mainly resulted from leaky transcriptions due to the insertions of T-DNAs in the introns. These mutants are semi-dwarfed and fertile and capable to be transformed. These intermediate mutants could be useful tools for future discovery and analyses of novel components regulating BR biosynthesis and catabolism via genetic modifier screen.